Teacher’s quality in public schools in Afghanistan: exploring the perceptions of public schools’ stakeholders - Amini, Mohammad Hussain (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Education degree in Educational Leadership and School Improvement, 2024.